Current treatment protocols can offer a normal or near‐normal quality of life in the majority of patients with non‐functioning pituitary adenomas. (11th December 2012) - Capatina, Cristina; Christodoulides, Constantinos; Fernandez, Alberto; Cudlip, Simon; Grossman, Ashley B.; Wass, John A. H.; Karavitaki, Niki
Summary: Objective: Non‐functioning pituitary adenomas (NFA) may be associated with significant morbidity. Published data on the quality of life (QoL) of patients with NFA are scarce and conflicting. In view of the discordant findings and the advances in the management of these subjects, we aimed to evaluate the QoL in patients with NFA followed up in a tertiary endocrine UK referral centre. Subjects and Methods: All consecutive patients with NFA attending the outpatient clinic in the Department of Endocrinology in Oxford over a 6‐month period ( n = 193) were offered 3 health‐related QoL questionnaires [Short Form 36 (SF36), Nottingham Health Profile (NHP), European Quality of Life Scale (EuroQoL)] to complete. Patient outcomes (response rate 93·3%) were compared with age‐related UK reference values. Results: None of the QoL scores in the SF‐36 or the 5 dimensions of health in the EuroQoL was different from the reference values. The visual analogue scale (VAS) score (EuroQoL) was slightly compromised ( P = 0·041). In the NHP questionnaire, males had no parameter significantly affected, whereas females performed worse in 1/6 areas (energy levels). Tumour recurrence was an independent predictor for compromised VAS score and for anxiety/depression (EuroQoL), and visual field defects for more frequent problems with interests/hobbies (NHP). Conclusions: Overall, the health‐related QoL and perception of subjective health in patients with NFA was not compromised to any major extent suggesting that we can now offer the prospect of treatment and replacement, which will provide a normal or near‐normal QoL. Specific groups are affected in various dimensions, necessitating measures to compensate for predisposing factors.